The Influence of Biodegradable Packaging and Consumer Awareness on Product Sustainability at Ascend Coffee and Tea Company: Pengaruh Kemasan Biodegradable dan Kesadaran Konsumen Terhadap Keberlanjutan Produk di Ascend Coffee and Tea Company - Angelica Natalia Waruwu; Dedy Lazuardi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study aims to analyze the influence of biodegradable packaging and consumer awareness on product sustainability at Ascend Coffee and Tea Company in Medan City. The background of the research is based on the increasing global and local attention to sustainability issues and the demand of the beverage industry to reduce dependence on single-use plastic packaging. The adoption of biodegradable packaging is seen as an important strategy in supporting an environmentally friendly brand image, while consumer awareness of sustainability issues is a key factor in encouraging more responsible purchasing behavior. This study uses a quantitative approach with a survey method through a questionnaire to Ascend Coffee and Tea Company consumers who have consumed the product in the last six months. The analysis was conducted to find out the extent to which biodegradable packaging variables and consumer awareness affect product sustainability, both partially and simultaneously. The results of this study are expected to make a theoretical contribution to the development of literature related to green marketing as well as practical implications for companies in implementing sustainable business strategies that are able to improve brand image, consumer loyalty, and long-term competitiveness.